Revisiting Legal Understanding of Wild Life as a Sustainable Value. The Case of Ukraine - ZAPARA, Svitlana I.; FOTINA, Hanna A.; KLOCHKO, Alyona M.; FOTINA, Tetiana I.; YATSENKO, Ivan V. (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019, 2019)
Animal rights in recent years occupy a significant place among the themes of general national discourse in Ukraine.  This year, under the pressure of the public in Ukraine, a law according to the humane attitude towards the "younger brothers" was adopted. But which rights do animals have? And what’s really going on? Legislation on animal protection is not executed even at the level where it is. How often do people who cause animal suffering in my country have the appropriate punishment? The report provides an analysis of the preconditions for reforming the attitude towards animals and their rights. The complexity of solving problem of humane attitude towards animals lies in the fact that it can not be regulated just based on the data of scientific experiments. Evaluation of the ability of animals to consciously feel pain, suffer, think, speak, understand themselves and the events around them is a difficult issue for many people. So, what is Animal Law? And what is Animal Ethic? Do we understand and recognize such concepts in my country?